Pengaruh Corporate Social Responsibility, Mekanisme GCG terhadap Manajemen Laba: Pada Perusahan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Rizki Zulkarnain; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2021)
The purpose of this study was to analyze the effect of CSR disclosure, independent commissioner, audit committee and managerial ownership on earnings management. The data used in this study are annual and financial reports in manufacturing companies listed on the indonesia stock exchange (idx) in the period 2015-2019. The method of taking data samples using purposive sampling method based on certain criteria. Based on the retrieval method obtained A sample of 195 companies. Hypothesis testing in this study uses multiple linear regression analysis. The results show that the independen commissioner, the audit committee has no effect on earnings management and the CSR disclosure of managerial ownership has an effect on earnings management.